Huntington disease exacerbates action impulses - Shiino, Shuhei; van Wouwe, Nelleke Corine; Wylie, Scott A.; Claassen, Daniel O.; McDonell, Katherine E. (Frontiers in Psychology, 2023)
Background Impulsivity is a common clinical feature of Huntington disease (HD), but the underlying cognitive dynamics of impulse control in this population have not been well-studied. Objective To investigate the temporal dynamics of action impulse control in HD patients using an inhibitory action control task. Methods Sixteen motor manifest HD patients and seventeen age-matched healthy controls (HC) completed the action control task. We applied the activation-suppression theoretical model and distributional analytic techniques to differentiate the strength of fast impulses from their top-down suppression. Results Overall, HD patients produced slower and less accurate reactions than HCs. HD patients also exhibited an exacerbated interference effect, as evidenced by a greater slowing of RT on non-corresponding compared to corresponding trials. HD patients made more fast, impulsive errors than HC, evidenced by significantly lower accuracy on their fastest reaction time trials. The slope reduction of interference effects as reactions slowed was similar between HD and controls, indicating preserved impulse suppression. Conclusion Our results indicate that patients with HD show a greater susceptibility to act rapidly on incorrect motor impulses but preserved proficiency of top-down suppression. Further research is needed to determine how these findings relate to clinical behavioral symptoms.